Comparison of nanodiamond coated quartz filter with commercial electropositive filters: Zeta potential and dye retention study. (31st October 2022) - Mandal, Soumen; Shaw, Greg; Williams, Oliver A.
Abstract: Diamond coated quartz(DQ) electropositive filters were compared with a few commercially available electropositive filters. The zeta potential of all the filters were measured and it was found that DQ had higher positive zeta potential over a wide pH range. Dye retention tests, using acid black II dye, performed on all the filters showed DQ to have higher retention. The study clearly showed that, under laboratory conditions, DQ has better performance compared to many commercial electropositive filters. Graphical abstract: Image 1